Study of NO2 and HCHO vertical profile measurement based on fast synchronous multi-axis differential optical absorption spectroscopy (FS MAX-DOAS) - J. Xu; J. Xu; A. Li; Z. Hu; H. Zhang; H. Zhang; M. Qin (Atmospheric Measurement Techniques)
This study investigates a multi-elevation fast synchronous multi-axis differential optical absorption spectroscopy (FS MAX-DOAS) observation system that can rapidly acquire trace gas profiles. It modifies the conventional MAX-DOAS method by sequentially scanning at elevation angles using motors. The new system incorporates a two-dimensional area array charge-coupled device (CCD) grating spectrometer, telescopes with a small field of view (< 1°), a high-speed shutter switching module, and a multi-mode multi-core fiber to enable multi-channel spectroscopy and significantly enhance the time resolution of the collected spectra (one elevation cycle within 2 min). When selecting the spectrometer grating, the impact of the spectral resolution on the detection of nitrogen dioxide (NO2) and formaldehyde (HCHO) by FS MAX-DOAS was simulated and analyzed. The optimal resolution range was determined to be 0.3–0.6 nm. The selection of the number of binning rows in the acquisition settings considers the signal-to-noise ratio of the pixels in each row to enhance the quality of the spectral data. Two-step acquisition is used for low elevation angles within one cycle to overcome the influence of variations in light intensity. A comparative test was conducted on outfield NO2 and HCHO measurements using differential optical absorption spectroscopy. Compared with the differential slant column densities (dSCDs) at each elevation angle measured by the MAX-DOAS system, the Pearson correlation coefficient of NO2 reached 0.9, while for HCHO it ranged mostly between 0.76 and 0.85. The results of the slant column concentration inversion indicate that the root mean square (rms) of the FS MAX-DOAS spectrum inversion can consistently be lower than that of MAX-DOAS over an extended period. The profile results show that the diurnal variation trend of the two systems was consistent, and because of the enhanced time resolution, the gas profile obtained by the former system can provide more detailed information. Compared with the near-ground NO2 concentration measured by the long-path DOAS (LP-DOAS) system, the daily variation trend shows a characteristic of being high in the morning and starting to decrease at noon, and the correlation coefficient between FS MAX-DOAS and LP-DOAS is higher (R = 0.901). The FS MAX-DOAS system can quickly and simultaneously obtain the vertical distribution profiles of NO2 and HCHO with high accuracy, providing a basis for mobile MAX-DOAS to achieve gas profile inversion.